Factors Influencing Financial Performance And Sustainability Of SMES: Evidence From Indonesia - Kusumastuti, Hesti; Aligarh, Frank (Jurnal AKSI (Akuntansi dan Sistem Informasi), 2024)
This study examines the impact of digital transformation, government support, human resource capacity, and innovation on the financial performance and sustainability of SMEs in the Soloraya region. The research method used is quantitative, with data collected through surveys using both Google Forms and paper questionnaires. A total of 137 respondents were analyzed using SEM-PLS in this study. The results indicate that digital transformation, human resource capacity, and innovation have a positive impact on financial performance. Additionally, government support, human resource capacity, innovation, and financial performance positively affect the sustainability of SMEs. However, digital transformation does not influence the sustainability of SMEs, and government support does not affect financial performance. These findings provide important insights for business practitioners and other stakeholders to enhance the performance and sustainability of SMEs in Indonesia.